(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Cinema, movie house, and pay-per-view are a few of the most trending entertainment services not only in Metro Manila but also in other parts of the Philippines. Horror, drama, romance, comedy, and science fiction are some of the most supported movie genres of movie goers. The researchers conceptualized “The Blockbuster House” by sharing different ideas and suggestions. Hence, the researchers built this kind of in-store type of business. The Blockbuster House is a type of business concept that differs from other cinema or food stores. Blockbuster Snack House offers different genres of movies that customers can pick from on Netflix. The offered foods by the business are chicken wings, chicken tenders, crispy chili, bacon maple wings, mozzarella sticks, French fries, super nachos, Monte Cristo sandwich, potato cheese rolls, and Filipino lumpia. Blockbuster Snack House also offers different soft drinks and mineral water. Each customer will pay P250 to watch the movie; this entrance fee includes consumable food or drink. This business is located at Block 65 Lot 01 Kudpyapi Street Lagro Subdivision, Novaliches, Quezon City. This feasibility study is proven profitable and unique in the market. This business can also upgrade as a business plan. The researchers proved that the Blockbuster Snack house is a place where everyone can hang out and watch movies. Despite the weakness and threats, the business can gain more profit and serve more customers. The formal outline of a company’s structure makes it easier to add a new position to the company and provides a flexible and ready means of growth. The researchers created their structure to improve their business decision-making process, sending information to a manager or employees responsible for completing business functions. The researchers analyzed the location of the store thoroughly, which should be easily seen by the customers. The researchers created a set of a questionnaire that includes the demographic profile of the respondents and different sets of questions regarding the business and distributed to the respondents. Due to the possible market demand, there will be more people who need to operate the business. If the business has enough budget, then it should hire workers to help operate the business. High-tech equipment is needed to produce products. Overall, the researchers are very confident that the business will be successful.